Clinical usefulness of combination therapy with polidocanol injection and argon plasma coagulation for gastric antral vascular ectasia. Issue 4 (6th March 2021) - Tamari, Hirosato; Oka, Shiro; Tanaka, Shinji; Hiyama, Yuichi; Ninomiya, Yuki; Kotachi, Takahiro; Boda, Tomoyuki; Yuge, Ryo; Urabe, Yuji; Kitadai, Yasuhiko; Chayama, Kazuaki
Abstract: Background and Aim: Gastric antral vascular ectasia (GAVE) causes gastrointestinal bleeding. The initial treatment for GAVE bleeding is endoscopic hemostasis, and currently, the most performed technique to achieve hemostasis is argon plasma coagulation (APC). However, APC is associated with a high recurrence rate. To overcome this limitation, we examined the outcomes of the combination therapy of APC and polidocanol injection (PDI) for treating GAVE. Methods: We retrospectively analyzed the outcomes of 15 consecutive GAVE patients treated with PDI + APC at Hiroshima University Hospital between November 2011 and September 2019 with respect to clinical characteristics, hemostatic efficacy, complications related to treatment, and recurrence rate. Results: The mean age of patients (4 men and 11 women) was 74 ± 8.4 years. Patients had comorbidities of liver cirrhosis (seven patients, 47%), chronic renal failure (seven patients, 47%), and autoimmune diseases (seven patients, 47%). Endoscopic hemostasis with PDI + APC was performed in all patients ( n = 15). The mean number of PDIs attempted to stop bleeding was 1.5 ± 0.8 (1–4), and the mean number of APCs attempted was 2.1 ± 1.2 (1–5). Complications related to treatment occurred in two patients (14%): ulceration in one patient and hematoma in another patient, both of whom were treated conservatively. Two patients (13%) had recurrences during the follow‐up period (average period, 42 months). Both were cured with additional treatment of PDI only. Conclusion: The combination therapy of PDI and APC is effective for GAVE with a low recurrence rate. Abstract : Argon plasma coagulation (APC) is effective for gastric antral vascular ectasia (GAVE) bleeding; however, the high recurrence rate is a problem. GAVE is a condition in which dilatation and proliferation of blood vessels are observed not only in the mucosal layer but also in the submucosal layer, and the high recurrence rate is considered to be because APC only treats vessels in the mucosal layer. We have traditionally treated the mucosal layer with APC and submucosal layer with polidocanol injection (PDI), and this combination therapy with PDI + APC for GAVE has a high hemostatic rate and low recurrence rate based on long‐term prognosis.